Hydroxychloroquine pleiotropic benefits: is there any evidence beyond rheumatological diseases? - Anil Pareek; Siddharth Nikam (International Journal of Research in Medical Sciences, 2024)
Once used as an antimalarial medication, hydroxychloroquine (HCQ) is now widely used to treat a variety of rheumatic diseases, including rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). HCQ has shown benefits in rheumatic diseases because of its anti-inflammatory and immunomodulatory properties. HCQ has demonstrated cardioprotective effects in rheumatic disorders, including SLE and RA. Recently, the role of inflammatory mediators has drawn a lot of attention in the pathophysiology of prediabetes, type 2 diabetes (T2D), diabetic complications and atherosclerotic cardiovascular diseases (ASCVD). In a prospective observational study of RA patients, taking HCQ for longer than four years, the incidence of diabetes has been found to be substantially decreased. In a mechanistic human pharmacodynamic study of T2D patients, HCQ showed improvements in insulin resistance and beta-cell function. These outcomes are associated with reductions in inflammatory markers such as interleukin 6 (IL6) and high-sensitivity C-reactive protein (hs-CRP). With its anti-hyperglycemic potential, anti-inflammatory, and pleiotropic effects (lipid-lowering, antiplatelet, antithrombotic) HCQ stands out as a therapeutic option that is affordable for patients with uncontrolled T2D who are at risk for complications. The pleiotropic benefits of HCQ extend beyond rheumatic diseases with potential in prediabetes, T2D and ASCVD.